Alaca Höyük Erken Tunç Çağı Krali Mezarları ve İkiz İdoller | Alaca Höyük Tombs of the Early Bronze Age and Twin Idols - Aykut ÇINAROĞLU (Arkhaia Anatolika, 2018)
The metal artifacts found in the King’s tombs of the Early Bronze Age at Alaca Höyük constitute one of the most important work groups within Near East archeology finds. We don’t know the identities of those buried in these tombs, which we can accept as members of a dynasty in Alaca Höyük during the Early Bronze Age III period. Because the writing hasn’t been used yet in this period. However, Alaca Höyük is a strong and rich center of a small kingdom, and the tombs belong to family members who have a local authority and belong to them. For this reason it is obvious that the graves belong to an elite group. In this article, a review of these objects and a period of time were made in the archaeological literature which is thought to be a furniture ornament found in the dead gifts of the elitist section buried in the graves, which are referred to as twin idols.